Study on students' background and attitudes towards computer skills in selected secondary schools in Segamat / Azizah Aris ... [et al.] - Aris, Azizah; Zainuddin, Ruhana; Kamarudin, Rafidah; Mohd. Daud, Norzaidi (Institute of Research, Development and Commercialization (IRDC), 2007)
This study is carried out to identify whether students ofdifferent backgrounds differ in their computer skills and at the same time to identify whether there is a correlation between students' attitudes and their computer skills. Thefinal objective of this study is to investigate which variable (background or attitudes) has a greater influence on the students' computer skills. All the Form Five students from the three different types ofschools in the Segamat district were chosen as samples. T-test, ANOVA, Pearson correlation and regression analyses were used to analyze the data. The study showed that there was a significant difference between the types ofschools the students were in, students' computer ownership and the students' computer club membership with their computer skills. In addition, the findings also revealed that there was a significant correlation between the computer attitude subscales with the students' computer skills. The multiple regression analysis showed that there was a relationship between the students' computer confidence, computer ownership, computer anxiety, school computer club membership and type ofschools towardsthe students'computer skills. However, we found that students' confidence in using the computer had a greater influence than computer ownership and other characteristics.